시맨틱 AI를 활용한 파일 검색 및 관리 소프트웨어 비즈니스 모델 제안: 서비스디자인 방법론을 중심으로 - 안우석(Woo-Seok Ahn); 안혜진(Hye-Jin An) (디지털콘텐츠학회논문지, 2024)
본 연구는 4D 더블 다이아몬드 디자인 프로세스 모델을 기반으로 시맨틱 AI를 활용한 파일 검색 및 관리 소프트웨어 비즈니스모델을 제안하였다. 1단계에서는 심층 인터뷰와 설문조사를 통해 대상자들이 필요한 정보를 제때 얻는 데 어려움을 겪고 있다는사실이 드러났다. 2단계에서는 TAM-SAM-SOM 시장분석, 경쟁사 분석, 페르소나 개발을 통해 고객, 고객의 니즈, 서비스의 핵심가치를 정의하였다. 3단계에서는 비즈니스 모델 캔버스(BMC)를 사용하여 가치 제안 비즈니스 모델의 9가지 요소를 구축하였다. 마지막으로 4단계에서는 네거티브 샘플링과 부분 표본화 기법을 활용하여 문서 내용 임베딩 생성 및 저장 방법을 도출하였고, 코사인 유사도 기반의 클러스터링 알고리즘 기술을 바탕으로 MVP를 개발하였다. 연구 결과는 AI의 실용적 접근을 통해 문서 관리프로세스를 개선하여 스타트업에 솔루션을 제공하고 AI 기반 비즈니스 모델의 분야에 공헌하게 된다. This study proposes a novel business model for file search and management software utilizing semantic artificial intelligence (AI), guided by the 4D Double Diamond Design Process. In-depth interviews and surveys highlighted users’ challenges with timely information retrieval. Customer needs and core service values were identified through TAM-SAM-SOM market analysis, competitor analysis, and persona development. The Business Model Canvas (BMC) framework was then used to outline the nine elements of the value proposition. Advanced techniques, including negative and partial sampling methods, were employed to create document embeddings, resulting in the development of a minimum viable product (MVP) using clustering algorithms based on cosine similarity. The findings demonstrate the practical application of AI in enhancing document management processes, providing a valuable solution for startups and contributing to the evolving field of AI-driven business models. KCI Citation Count: 0